Importance of advective mass transfer and sediment surface area for streambed microbial communities. (7th November 2016) - Mendoza‐Lera, Clara; Frossard, Aline; Knie, Matthias; Federlein, Laura L.; Gessner, Mark O.; Mutz, Michael
Summary: Variability of flow and shear stress cause local sorting and a patchy distribution of grain size in streambed sediments. Sediment microbial communities can be affected by the resulting heterogeneity because grain size determines (i) the sediment surface area available for microbial colonisation and (ii) the hydraulic conductivity and hence advective mass transfer of solutes and redox partners. However, the relative influence of the two factors on sediment microbial communities is not clear. We performed an experiment in 12 indoor flumes with three types of sediment: gravel (2–8 mm), a sand–gravel mixture (25 and 75% by mass) and sand (0.2–0.8 mm) in four flumes each. The sediments differed in both advective mass transfer (gravel > sand–gravel mixture = sand) and surface area (gravel < sand–gravel mixture < sand). We added a microbial inoculum to each flume. After 40 days of colonisation, we collected sediment samples to characterise the sediment microbial community by determining the abundance of bacteria and algae, respiration rates and potential enzyme activities. The consistent pattern found across all microbial variables showed that grain size clearly influences sediment microbial communities through advective mass transfer, although an influence of sediment surface area cannot be ruled out: (i) all variables were highest in gravel when expressed per surface area but differed little between sand and the sand–gravel mixture and (ii) all variables were similarly high in gravel and sand or the sand–gravel mixture on a volumetric basis, in spite of a greatly reduced surface area in gravel. Overall, our findings suggest that grain‐size distribution in streams should be taken into account in analyses of streambed microbial communities, especially if it has an effect on advective mass transfer.